Rehabilitation of Rural Finance Institutions : Lessons from Benin and the African Experience - Turtiainen, Turto (2012)
Most attempts to develop financial markets and rural credit institutions in Africa have performed poorly, not satisfying the demand for savings and credit services in the rural areas. In many cases, however, the institutions continue to exist and could be revived, enlarged, or made more efficient if suitable programs to help them can be worked out. This note reviews the strategies and measures that can be used to rehabilitate rural finance institutions, based on the successful rehabilitation program in Benin and some other cases in Africa. Rehabilitation of a rundown rural finance institution takes several years, but it can be organized in phases, first concentrating on emergency measures to save the institution from bankruptcy, and then planning and implementing the actions for a longer term recovery process.